2016
DOI: 10.29313/gmhc.v4i1.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Faktor Risiko dan Karakteristik Gejala Klinis dengan Kejadian Pneumonia pada Balita

Abstract: AbstrakPneumonia masih merupakan penyebab kesakitan dan kematian pada balita di negara berkembang.Faktor risiko pneumonia yang selalu ada (definite risk factor) meliputi gizi kurang, bayi berat lahir rendah (BBLR), tidak memberikan ASI, polusi udara di dalam ruang, dan pemukiman padat. Gejala pneumonia bervariasi bergantung pada usia penderita dan penyebab infeksinya. Tujuan penelitian ini menilai hubungan faktor risiko dan karakteristik gejala klinis dengan kejadian pneumonia pada balita. Penelitian cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
1
1
3
Order By: Relevance
“…The results showed that the incidence of toddler pneumonia in male toddlers was greater than that of women. This research is in line with previous research by Garina, Putri, & Yuniarti (2016) which stated that the incidence of pneumonia in children under five was dominated by male toddlers as much as 59%. The incidence of pneumonia is more common in male than female.…”
Section: Overview Of Pneumonia In Toddlers In West Java Provincesupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that the incidence of toddler pneumonia in male toddlers was greater than that of women. This research is in line with previous research by Garina, Putri, & Yuniarti (2016) which stated that the incidence of pneumonia in children under five was dominated by male toddlers as much as 59%. The incidence of pneumonia is more common in male than female.…”
Section: Overview Of Pneumonia In Toddlers In West Java Provincesupporting
confidence: 93%
“…Babies born with low birth weight have imperfect organs including the respiratory tract (Sary, 2017). The results of the study were not in line with the research of Garina, Putri, & Yuniarti (2016) which showed that there was no association between LBW and toddlers pneumonia. This is because several other conditions can also affect the incidence of pneumonia in toddlers, such as the risk factors studied in the study.…”
Section: Relationship Between Low Birth Weight (Lbw) and Pneumonia On Toddlers In West Java Provincecontrasting
confidence: 86%
“…Stunting terjadi sebagai dampak dari malnutrisi kronis selama 1.000 hari pertama kehidupan yang dapat disebabkan oleh bebagai faktor yaitu pendidikan kurang yang dipengaruhi oleh orangtua, apabila pendidikan orangtua tinggi berpengaruh terhadap pengasuhan dan secara langsung memberikan motivasi kepada anak untuk belajar secara optimal karena terdapat asuhan orangtua yang baik. (10)(11) Untuk memenuhi kebutuhan gizi yang cukup dapat berpengaruh pada pendapatan atau penghasilan orangtua. Penghasilan merupakan hasil dari penjualan barang dagangan, pelaksanaan kepada pelanggan atau klien untuk memperoleh penghasilan.…”
Section: Cunclassified
“…Hal ini dijelaskan bahwa anak di bawah usia 1 tahun memiliki saluran napas yang lebih sempit sehingga infeksi saluran napas akan lebih mudah terjadi. 9 Menurut penelitian yang dilakukan oleh Hartati et al, 10 status gizi dan riwayat pemberian ASI eksklusif juga berpengaruh terhadap faktor usia.…”
Section: Hasil Dan Bahasan Karakteristik Pasien Bronkopneumoniaunclassified